Porous Copper‐PTFE Hybrid Electrocatalyst for CO2 Reduction with High C2+ Selectivity - Yoshitomo Seki; Mamiko Nakabayashi; Masakazu Sugiyama; Tsutomu Minegishi (ChemElectroChem)
Abstract The electrochemical CO2 reduction reaction (CO2RR) to ethylene (C2H4) is one of the most promising approaches to obtaining value‐added C2+ hydrocarbons without net CO2 emission. However, issues still to be solved for practical use include the improvement of Faradaic efficiency (FE) towards C2H4, electrode durability, and suppression of competitive hydrogen evolution reaction (HER). In this work, hydrophobic polymer, polytetrafluoroethylene (PTFE), added porous Cu electrocatalysts were firstly and successfully prepared on gas diffusion layer, and the significant enhancement of FEs toward C2+ products, especially C2H4, and durability were found. CO2RR test in flow cell as a gas diffusion electrode (GDE) revealed that the GDE with porous Cu electrocatalysts showed higher FE(C2H4) to FE(CO) while significant HER and instability issues remained. Further modification by PTFE to form porous Cu‐PTFE hybrid structure significantly decreased FE(H2) to 11.6 % in minimum, enhanced FE(C2H4) to 51.1 % in maximum and raised durable CO2RR for over 24 hours under current density of −300 mA cm−2. PTFE addition should form a secured pathway for gas species, including both reactant and product which was beneficial for durable and selective C2H4 production. This work highlights chemical engineering aspects of CO2RR including the transportation of reactants and products.